HUBUNGAN STATUS SOSIAL KELUARGA DAN PRESTASI BELAJAR DASAR-DASAR OTOMOTIF DENGAN MINAT MELANJUTKAN KE PERGURUAN TINGGI SISWA KELAS X SMK TAMANSISWA JETIS YOGYAKARTA TAHUN AJARAN 2014/ 2015 - Rusman Hadi; Tarto Sentono (Universitas Sarjanawiyata Tamansiswa, 2015)
This research were aimed at: (1) to know relationship social status of the family with interest continuing to college students of class X SMK Tamansiswa Jetis Yogyakarta in the academic years 2014/2015; (2) to know relationship the achievements of automotive basics learning with interest continuing to college students of class x SMK Tamansiswa Jetis Yogyakarta in the academic years 2014/2015; (3) to know relationship social status of the family and the achievements of automotive basics learning with interest continuing to college students of class x SMK Tamansiswa Jetis Yogyakarta in the academic years 2014/2015. This research was correlational research and categorized into ex post facto research. The population research is the grade of automotif skill competencies class X SMK Tamansiswa Jetis who totalled 114 students. While sample totalled 88 student turning using the formula Isacc and Michael. Technique for taking sample used in this study was Proportionate Stratified Random Sampling. Techniques for collecting data in this study were questionnaire and documentation. Item validity was calculated by using product moment correlation. Item Reliability was computed by using alpha formula. Techniques for analyzing data used in this study were partial correlation and bivariate regression analyses. Before those, prerequisite analysis used in this study was to test normality, linearity, multicolinearity.Based on the data analysis, it was found that the results of this research: (1) there is a positive and significant relationship of social status of the family with interest continuing to college students; (2) there is a positive and significant relationship of achievements of automotive basics learning with interest continuing to college students; (3) there is a positive and significant relationship of social status of the family (x1) and the achievements of automotive basics learning (x2) with interest continuing to college students (y).